Nilai Sosial dalam Cerpen Ngantén Karya Komang Adnyana - Saleh, Ifrado M; Suardiana, I Wayan; Duana Sutika, I Nyoman (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2025)
This research, titled